Location of single-family house settlements from 60s to 80s of 20th century in Wrocław’s urban space - Napieralska, Zuzanna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
Housing construction in the second half of the twentieth century was intensively developed in Europe and in the whole world. The expansion of industry and the development of cities, initiated at the turn of the 19th and 20th centuries, had a huge impact on urban planning, the creation of housing estates and their location in the city structure. In Wrocław, new post-war housing estates, including single-family housing, were inscribed in the existing urban layout of the city from the inter-war period. Wrocław in the 1920s and 1930s increased its area several times. New, connected areas were intended, above all, for housing construction. After the war, Wroclaw’s planners drew on pre-war plans to expand the city, but also updated and modified them, adapting them to the current needs of residents. The article focuses on the urban development of Wrocław from the 1960s to the 1980s in the field of organized single-family housing.